2014
DOI: 10.1159/000362231
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acupuncture in in vitro Fertilization: A Systematic Review and Meta-Analysis

Abstract: Background/Aims: In recent years, acupuncture has become more and more popular in the management of subfertility. The aim of this study was to evaluate the impact of acupuncture during in vitro fertilization (IVF) treatment on the outcomes of clinical pregnancy in published randomized studies. Methods: This is a systematic review and meta-analysis. Data sources used were MEDLINE, Embase, Web of Knowledge and the Chinese Biomedical Database. Results: There was no statistically significant difference between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 36 publications
1
48
0
3
Order By: Relevance
“…The relevance of shamcontrolled trials in IVF research has been debated at length (see Manheimer 57 for a comprehensive overview), particularly in view of the fact that pregnancy is an objective outcome measure for which blinding is less critical. [58][59][60][61] When sham-controlled trials are included, the three latest systematic reviews demonstrate no pooled benefit of acupuncture [10][11][12] although Shen et al 12 did find evidence of benefit with follicular phase treatment plus treatment around ET. Manheimer et al 11 reported that acupuncture treatment appears to be more successful in studies with lower baseline pregnancy rates.…”
mentioning
confidence: 99%
“…The relevance of shamcontrolled trials in IVF research has been debated at length (see Manheimer 57 for a comprehensive overview), particularly in view of the fact that pregnancy is an objective outcome measure for which blinding is less critical. [58][59][60][61] When sham-controlled trials are included, the three latest systematic reviews demonstrate no pooled benefit of acupuncture [10][11][12] although Shen et al 12 did find evidence of benefit with follicular phase treatment plus treatment around ET. Manheimer et al 11 reported that acupuncture treatment appears to be more successful in studies with lower baseline pregnancy rates.…”
mentioning
confidence: 99%
“…In addition to increasing blood flow to the uterus and ovaries, acupuncture increases endometrial and follicular receptivity, which, in turn, improves the quality of oocytes produced by the follicles, and also helps repair the endometrial lining, which is needed for implantation. 3,6,7 Increasing blood flow is influenced by vascular endothelial growth factor (VEGF), which promotes angiogenesis. 9 It has been reported that acupuncture can reduce uterine contractility to prevent embryo expulsion after ET.…”
Section: Mechanisms Of Acupuncture In Ivfmentioning
confidence: 99%
“…9 It has been reported that acupuncture can reduce uterine contractility to prevent embryo expulsion after ET. 3,6,7 Increasing the quality of oocytes might be related to tumor-necrosis factor-a (TNF-a) levels, wherein acupuncture could reduce TNF-a levels in follicular fluid, reduce apoptosis of granulosa cells, and improve oocyte quality, thereby, increasing pregnancy rates in patients undergoing IVF. 16 The effect of acupuncture on increasing IVF success is influenced by immune-system modulation.…”
Section: Mechanisms Of Acupuncture In Ivfmentioning
confidence: 99%
See 2 more Smart Citations